Visual Communication and Its Relevance to Art Education on Murals at Tugu Tunas, Semarang City (Catharsis, 2022)
The existence of a mural at Tugu Tunas has an important role as a medium of communication in public spaces. This mural is unique because it is applied to the monument field. This is different from most murals in general, bearing in mind that most murals occupy the walls of buildings with large fields of images. The purpose of this research is to analyze visual communication and its relevance to art education in the mural at Tugu Tunas, Semarang. This study uses a qualitative method with a phenomenological approach. Sources of data obtained from the process of field observations and interviews with a number of informants. Validating the data in this study used three stages of validating phenomenological data. The main idea in making or having a monument is "the desire to display Semarang's local culture which is visualized through murals on the monument. Through a semiotic study, the message to be conveyed through the mural on the monument is appropriate. This suitability means that the translation of concepts from the government and artists has accuracy. Artists are able to translate the symbols attached to the murals on the monument to be depicted. Communication disorders in this study occur in elements of works of art and the art public. The public gains artistic and aesthetic knowledge as well as experience when they see and observe deeply the existence of murals in the Semarang city monument.